Ultrasound-assisted extraction using response surface methodology for extracting flavonoids from Padina australis - Bina Lohita Sari,; Tri Saptari Haryani,; Triastinurmiatiningsih,; Dinda Rizki Amalia, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Seaweed or sea macroalgae are rich in potential compounds which can be used for the treatment of disease. Padina australis is one of the important brown macroalgae classes (Phaeophyes). One of the bioactive compounds of P. australis is a phenolic compound and its derivatives (flavonoid). In this research, P. australis was collected from Bayah Beach, Banten, Indonesia. For the extraction flavonoids from P. australis, ultrasound-assisted extraction (UAE) was employed. In this study, a three-level Box-Behnken design (BBD) and the response surface methodology (RSM) were employed to obtain the optimal combination of extraction conditions. The effects of several independent variables including temperature (30, 50, 70 ℃), extraction time (20, 40, 60 min) and ethanol concentration (30, 50, 70%) were investigated. The result showed that RSM was an accurate and reliable method in predicting the total flavonoid content with R2 value of 0.9935. The optimal UAE conditions for the highest yield of total flavonoid content were 49.70 ℃ in temperature, process time under 44.03 min, and 47.80% ethanol with 0.2162% total flavonoid content. Under the above conditions, the experimental value of total flavonoid content was 0.2144+ 0.0035%. The predicted and experimental values for total flavonoid from brown algae P. australis were not significant differences, it indicating that the developed models are accurate. Therefore, UAE using RSM is effective for the extraction of flavonoid from P. australis.